POLICY PUBLIC IMPLEMENTATION: PROBLEM OF POLICY IMPLEMENTATION IN AFRICA (SUSTAINABLE DEVELOPMENT GOALS) - Seidi, Dembael (Aliansi, 2024)
The African continent is at a crossroads caused by economic recession, crime, corruption and incompetence of leaders leading to insecurity and poverty. This is the best time to join forces in finding solutions to the challenges facing sustainable development in Africa. This study seeks to assess difficulties in implementing policies and the Sustainable Development Goals (SDGs) with specific reference to Africa. This article is supported by a thorough literature review to ensure that the purpose of the review was clear. A typical literature review method includes several steps including searching, collecting, prioritizing and reading with the aim of identifying important issues and themes which are then presented and critically examined. Africa must fight procedural deviations to properly align the desired objectives. Benua Afrika berada di persimpangan jalan yang disebabkan oleh resesi ekonomi, kejahatan, korupsi dan ketidakmampuan para pemimpin yang menyebabkan ketidakamanan dan kemiskinan. Ini adalah waktu terbaik untuk bergabung dalam mencari solusi atas tantangan yang dihadapi pembangunan berkelanjutan di Afrika. Studi ini berupaya menilai kesulitan dalam mengimplementasikan kebijakan dan Tujuan Pembangunan Berkelanjutan (SDGs) dengan referensi khusus ke Afrika. Artikel ini didukung oleh tinjauan literatur menyeluruh untuk memastikan bahwa tujuan dari tinjauan itu jelas. Metode tinjauan pustaka yang khas mencakup beberapa langkah termasuk mencari, mengumpulkan, memprioritaskan, dan membaca dengan tujuan mengidentifikasi masalah dan tema penting yang kemudian disajikan dan diperiksa secara kritis. Afrika harus melawan penyimpangan prosedural untuk menyelaraskan tujuan yang diinginkan dengan benar.